(untitled) (Web of Teachers: Inderscience Research, 2024)
This article analyzes professional culture formation in primary school teachers as a foundation of professional maturity, pedagogical thinking, professional-methodical preparedness, knowledge related to professional activities, organization of the educational process, and self-development strategies.